8-Hydroxyquinoline-based inhibitors of the Rce1 protease disrupt Ras membrane localization in human cells. Issue 2 (15th January 2016) - Mohammed, Idrees; Hampton, Shahienaz E.; Ashall, Louise; Hildebrandt, Emily R.; Kutlik, Robert A.; Manandhar, Surya P.; Floyd, Brandon J.; Smith, Haley E.; Dozier, Jonathan K.; Distefano, Mark D.; Schmidt, Walter K.; Dore, Timothy M.
Graphical abstract: Abstract: Ras converting enzyme 1 (Rce1) is an endoprotease that catalyzes processing of the C-terminus of Ras protein by removing -aaX from the CaaX motif. The activity of Rce1 is crucial for proper localization of Ras to the plasma membrane where it functions. Ras is responsible for transmitting signals related to cell proliferation, cell cycle progression, and apoptosis. The disregulation of these pathways due to constitutively active oncogenic Ras can ultimately lead to cancer. Ras, its effectors and regulators, and the enzymes that are involved in its maturation process are all targets for anti-cancer therapeutics. Key enzymes required for Ras maturation and localization are the farnesyltransferase (FTase), Rce1, and isoprenylcysteine carboxyl methyltransferase (ICMT). Among these proteins, the physiological role of Rce1 in regulating Ras and other CaaX proteins has not been fully explored. Small-molecule inhibitors of Rce1 could be useful as chemical biology tools to understand further the downstream impact of Rce1 on Ras function and serve as potential leads for cancer therapeutics. Structure–activity relationship (SAR) analysis of a previously reported Rce1 inhibitor, NSC1011, has been performed to generate a new library of Rce1 inhibitors. The new inhibitors caused a reduction in Rce1 in vitro activity, exhibited low cell toxicity, and induced mislocalization of EGFP-Ras from the plasma membrane in human colon carcinoma cells giving rise to a phenotype similar to that observed with siRNA knockdowns of Rce1 expression. Several of the new inhibitors were more effective at mislocalizing K-Ras compared to a potent farnesyltransferase inhibitor (FTI), which is significant because of the preponderance of K-Ras mutations in cancer.